2022
DOI: 10.11604/pamj.2022.41.184.28549
|View full text |Cite
|
Sign up to set email alerts
|

Fibromatose desmoïde mammaire: à propos de deux cas et revue de la littérature

Abstract: La fibromatose mammaire est une tumeur mammaire bénigne d´origine mésenchymateuse, elle représente 0.2% des tumeurs du sein. Cet article relate deux observations de fibromatose mammaire étayant ses particularités diagnostiques, morphologiques, thérapeutiques et évolutives. Dans les deux cas, la tumeur mime sur le plan clinique et radiologique un cancer. La confirmation diagnostique est obtenue par une preuve histologique. La fibromatose mammaire se caractérise par une évolution locale et une tendance à la réci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Historically, achieving tumor-free margins was considered the "Holy Grail" of any surgical approach for desmoid tumors in general and breast desmoid tumors in particular. Some studies even suggested a "safety margin" of 2-3 cm [109,110]. However, the real impact of tumor-free margins on recurrence rates is controversial, with conflicting data regarding their impact on the risk of recurrence in breast desmoid tumors and desmoid tumors in general [2,100].…”
Section: Breast Desmoid Tumorsmentioning
confidence: 99%
“…Historically, achieving tumor-free margins was considered the "Holy Grail" of any surgical approach for desmoid tumors in general and breast desmoid tumors in particular. Some studies even suggested a "safety margin" of 2-3 cm [109,110]. However, the real impact of tumor-free margins on recurrence rates is controversial, with conflicting data regarding their impact on the risk of recurrence in breast desmoid tumors and desmoid tumors in general [2,100].…”
Section: Breast Desmoid Tumorsmentioning
confidence: 99%